Antibiotic-Resistant Extended Spectrum ß-Lactamase- and Plasmid-Mediated AmpC-Producing Enterobacteriaceae Isolated from Retail Food Products and the Pearl River in Guangzhou, China - Ye, Qinghua; Wu, Qingping; Zhang, Shuhong; Zhang, Jumei; Yang, Guangzhu; Wang, Huixian; Huang, Jiahui; Chen, Mongtong; Xue, Liang; Wang, Juan (Frontiers in Microbiology, 2017)
We conducted a survey in 2015 to evaluate the presence of extended spectrum β-lactamase (ESBL)- and plasmid-mediated AmpC-producing Enterobacteriaceae in retail food and water of the Pearl River in Guangzhou, China, as well as their antibiotic resistance profiles. Samples (88 fresh food samples and 43 water samples) from eight different districts were analyzed by direct plating and after enrichment. Multidrug-resistant strains were found in 41.7% and 43.4% of food and water samples, respectively. ESBLs were found in 3.4% and 11.6% of food and water samples, respectively, and AmpC producers were found in 13.6% and 16.3% of food and water samples, respectively. Molecular characterization revealed the domination of blaCTX-M genes; plasmidic AmpC was of the type DHA-1 both in food and water samples. 13 of 51 β-lactamase-producing positive isolates were detected to be transconjugants, which readily received the β-lactamase genes conferring resistance to β-lactam antibiotics as well as some non-β-lactam antibiotics. These findings provide evidence that retail food and the river water may be considered as reservoirs for the dissemination of β-lactam antibiotics, and these resistance genes could readily be transmitted to humans through the food chain and water.